"To achieve perfect clarity of expression, that is my aim“: Zum Verhältnis von Tradition und Neuerung in Benjamin Brittens "War Requiem“ - Rowold, Helge (Die Musikforschung, 1999)
A characteristic attribute of the semantics which underly Benjamin Britten's oeuvre is the deliberate recourse to musical semantems of Renaissance and Baroque. In the "War Requiem", melodic texture is subject to constructive principles inspired by (1) Alban Berg's technique to handle symmetrical interval cycles as it can be found in Berg's opera "Lulu", and (2) the contrapuntal rules of western european modality and solmization controlling ambitus and diastematics of melodic progressions. The a cappella "Requiescant in pace" concluding the work is shown to be a locrian organum strucuture, probably representing Britten's hope for the pacifying power of humanistic tradition.